IMPLEMENTATION OF INCLUSIVE EDUCATION FOR INDIVIDUALS WITH SPECIAL NEEDS - Suhardi, Suhardi; Fitriani, Wahidah; Khairat, Annisaul (Publikasi dan UKI Press UKI Toraja., 2023)
The problem in this research is that education for children with special needs and inclusive education in Indonesia has so far received little attention and cannot be handled optimally. So this study aims to find out about the quality of education in Indonesia, the development of children with special needs who have differences from normal children in general, both in terms of physical, mental, intellectual and social, and in inclusive education. The method used in this research is library research, using books and other sources. The results of the study explain that as citizens, children with special needs (ABK) and inclusive education have the same rights and obligations as citizens and have the same treatment, including in obtaining education.